1995
DOI: 10.1901/jaba.1995.28-417
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse and Neglect by Parents With Disabilities: A Tale of Two Families

Abstract: Two families, in which the children had been placed in foster care due to abuse and neglect by parents who had disabilities, were studied. In the first case, the mother was instructed in skills that our assessment suggested were important for her child's survival. The mother readily acquired and applied these skills, a fact reflected both in changes in her behavior and in changes in the child's well-being. In the second case, the parent's incremental resumption of child custody was made contingent upon complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…Many applied behavior analysts have also worked to prevent such important social ills as sexual abuse, abduction, and child abuse and neglect through procedures that include behavioral skills training and feedback (e.g., Greene, Norman, Searle, Daniels, & Lubeck, 1995;Miltenberger et al, 1999;Miltenberger & Thiesse-Duffy, 1988;Tertinger, Greene, & Lutzker, 1984), as well as ecobehavioral approaches that stress the importance of variables within the family and local community (e.g., socioeconomic status, family stressors; see Lutzker & Campbell, 1994). More recently, behavioral approaches to parent training have been used to prevent abuse and promote the well-being of foster children (e.g., Van Camp, Borrero, & Vollmer, 2003).…”
Section: Applied Behavior Analysismentioning
confidence: 99%
“…Many applied behavior analysts have also worked to prevent such important social ills as sexual abuse, abduction, and child abuse and neglect through procedures that include behavioral skills training and feedback (e.g., Greene, Norman, Searle, Daniels, & Lubeck, 1995;Miltenberger et al, 1999;Miltenberger & Thiesse-Duffy, 1988;Tertinger, Greene, & Lutzker, 1984), as well as ecobehavioral approaches that stress the importance of variables within the family and local community (e.g., socioeconomic status, family stressors; see Lutzker & Campbell, 1994). More recently, behavioral approaches to parent training have been used to prevent abuse and promote the well-being of foster children (e.g., Van Camp, Borrero, & Vollmer, 2003).…”
Section: Applied Behavior Analysismentioning
confidence: 99%
“…Returning to a health-related theme, research has demonstrated how to use prompts, incentives, and problem-solving procedures to increase low-income families' use of dental services (Reiss & Bailey, 1982). Many applied behavior analysts have also worked to prevent such important social ills as sexual abuse, abduction, child abuse, and neglect through procedures that include behavioral skill training and feedback (Greene, Norman, Searle, Daniels, & Lubeck, 1995;Miltenberger, et al, 1999;Miltenberger & Thiesse-Duffy, 1988;Tertinger, Greene, & Lutzker, 1984), as well as an ecobehavioral approach that stresses the importance of ecological variables within the family and local community (e.g., socioeconomic status, family stressors; Lutzker & Campbell, 1994). More recently, behavioral approaches to parent training have been used to prevent abuse and promote the well-being of foster children (Van Camp, Borrero, & Vollmer, 2003).…”
Section: Wealthmentioning
confidence: 99%
“…The practice may have its roots in the mystique and presumed relevance of psychological opinion, the dubious assumption that psychological assessment results are predictive of minimally adequate parenting, or the absence of any better alternative. In any case, the practice may become more widely challenged as more direct measures of parenting competence are developed and as evidence mounts that psychological conditions or diagnoses (e.g., mental retardation) do not necessarily preclude such competence (d. Greene, Norman, Searle, Daniels, & Lubeck, 1995).…”
Section: Psychological Assessmentsmentioning
confidence: 99%
“…ON THE BASIS OF ESTABLISHED STANDARDS: THE EXAMPLE OF NUTRITIOUS MEALS Greene et al (1995) reported an experimental case study of a developmentally disabled mother (IQ = 71) and her son who had been repeatedly hospitalized for failure to thrive. There is evidence that such parents are at particular risk for losing custody of their children, in part because of cultural biases regarding their parenting ability (Taylor, Norman, Murphy, [ellinek, Quinn, Poitrast, & Goshko, 1991).…”
Section: Quantifying the Continuum Of Competent Parentingmentioning
confidence: 99%
See 1 more Smart Citation